2014
DOI: 10.1098/rspb.2013.1743
|View full text |Cite
|
Sign up to set email alerts
|

ASPM and mammalian brain evolution: a case study in the difficulty in making macroevolutionary inferences about gene–phenotype associations

Abstract: Identifying the genetic basis of adaptive phenotypes can be a significant step towards understanding how that phenotype evolved. With the increased availability of interspecific molecular data, an approach to uncover such genes has been to search for signatures of adaptive evolution at the molecular level. Many analyses have adopted a candidate gene approach, focusing on genes with important developmental roles. One such candidate gene is ASPM, which is involved in neurogenesis and associated with major neurol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 11 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…There are few human specific genes such as SRGAP2C 5 , ARHGAP11B 6 or NOTCH2NL 7 that recently appeared through gene duplication in the Homo lineage 8 and remarkably their expression in the mouse brain increases cortical development 6,7,9,10 . In addition, several genes involved in brain function display accelerated evolution of their coding regions in humans, for example FOXP2 has been associated with verbal apraxia and ASPM with microcephaly 11,12 . Functional studies also showed that mice carrying a "humanized" version of FOX2 display qualitative changes in ultrasonic vocalization 13 .…”
Section: Introductionmentioning
confidence: 99%
“…There are few human specific genes such as SRGAP2C 5 , ARHGAP11B 6 or NOTCH2NL 7 that recently appeared through gene duplication in the Homo lineage 8 and remarkably their expression in the mouse brain increases cortical development 6,7,9,10 . In addition, several genes involved in brain function display accelerated evolution of their coding regions in humans, for example FOXP2 has been associated with verbal apraxia and ASPM with microcephaly 11,12 . Functional studies also showed that mice carrying a "humanized" version of FOX2 display qualitative changes in ultrasonic vocalization 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Statistical association between selection on a functional gene and changes in phenotype are an important indication for exploring the genetic basis of adaptive phenotypes [ 21 , 48 ]. Regressions revealed a significant positive association between relative brain size (EQ) and evolutionary rates for ASPM and CDK5RAP2 but not for WDR62 and CEP152 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, no association was found in the ASPM gene when only the two exons (approx. 60% of the transcribed ASPM protein) were examined in our previous study [ 20 ], which was questioned by Montgomery et al [ 21 ]. However, when the 22 exons, accounting for 90.34% of the transcribed ASPM protein, were used in this study, it was striking and interesting to find a significant association between root-to-tip ω of ASPM and cetacean EQ ( R 2 = 0.304, P = 0.046, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While initial studies did find evidence for positive selection across some primate lineages for several genes (reviewed in Gilbert et al, 2005), the correlation with changes in brain size was usually not explicitly tested, impeding the interpretation of these findings (Woods et al, 2005; Montgomery et al, 2014). …”
Section: Examples Of Genes Correlating With Brain Size Changesmentioning
confidence: 99%